Dyscalculia : a love story of epic miscalculation - Felix, Camonghne (One World, 2023)
"Dyscalculia is an exquisite and raw booklength essay that follows Camonghne Felix's journey to survey and reconfigure the pieces of a broken heart in order to rebuild one that is entirely her own. Felix uses her childhood "dyscalculia"-a disorder that makes it difficult to learn math-as a metaphor for the consequences of her miscalculations in intimacy. Dyscalculia negotiates the misalignments of perception and reality, love and harm, and the politics of heartbreak, both romantic and familial"--